Morphometric Assessment of Sellar Turcica: Tertiary Neurocenter study from Nepal. - Bishokarma, Suresh; Dahal, Mohit Raj; Adhikari, Nawaraj; Bhusal, Suraj; Parajuli, Shamin; Gurung, Suraj; Rai, Shiwani; Chowhan, Rushel; Shrestha, Sunita; Thulung , Suraj (Nepal Journal of Neuroscience, 2023)
Introduction: The sella turcica (ST) is a vital structure located in the median position within the middle cranial fossa and is frequently utilized in cephalometric for assessing craniofacial features. However, there is limited literature available regarding cephalometry of the ST in Nepal. Consequently, this study aimed to establish the normal dimensions of the ST in the Nepalese population and explore the potential difference in radio-morphometric measurement among sexes. Materials & Methods: This study encompassed a descriptive, cross-sectional chart review conducted at the Upendra Devkota Memorial National Institute of Neurological and Allied Sciences over a three-month period. Morphometric assessment of the ST was performed using computed tomography scans. A single radiologist employed an EV Insite DICOM viewer to measure and record the length, depth, and antero-posterior diameter of the ST. Independent-Samples t-test was employed to compare the means between sexes, and a significance level of p < 0.05 was considered statistically significant. Results: Among the 385 cases analyzed, 199 were male (51.8%) and 185 were female (48.2%), resulting in a male-to-female ratio of 1.07:1. The age range of the patients was 20 to 87 years, with a mean age of 44.5 ± 18.5 years. The mean dimensions of the sella turcica were determined as 9.32 mm for length, 7.07 mm for depth, and 10.29 mm for the antero-posterior diameter. Conclusions: The findings of this study indicate that the ST dimensions in the Nepalese population are relatively smaller compared to those reported in various other countries. Additionally, no statistically significant differences were observed in ST dimensions between males and females within the Nepalese population. These results emphasize the importance of considering populationspecific variations when utilizing cephalometric measurements and provide valuable reference standards for future studies and accurate assessment of craniofacial morphology in the Nepalese population.